2015
DOI: 10.1101/cshperspect.a020545
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Function in Central Nervous System Development and Plasticity

Abstract: The nervous system comprises a remarkably diverse and complex network of different cell types, which must communicate with one another with speed, reliability, and precision. Thus, the developmental patterning and maintenance of these cell populations and their connections with one another pose a rather formidable task. Emerging data implicate microglia, the resident myeloid-derived cells of the central nervous system (CNS), in the spatial patterning and synaptic wiring throughout the healthy, developing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
272
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(278 citation statements)
references
References 141 publications
(162 reference statements)
4
272
0
2
Order By: Relevance
“…Microglia have traditionally been thought of as the immune cells of the brain, but a body of recent research suggests that these cells may also play important roles in nonpathological brain function, specifically the pruning and alteration of synapses (90). Animal live-imaging studies have demonstrated that microglia interact dynamically with synapses undergoing developmental pruning (93,94).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia have traditionally been thought of as the immune cells of the brain, but a body of recent research suggests that these cells may also play important roles in nonpathological brain function, specifically the pruning and alteration of synapses (90). Animal live-imaging studies have demonstrated that microglia interact dynamically with synapses undergoing developmental pruning (93,94).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular processes involved in synaptic elimination include localized, mitochondrial-mediated apoptosis in dendritic spines (82)(83)(84) that trigger immune functions mediated by the complement system (85,86), which, in turn, initiate the removal of synaptic detritus by microglia (87)(88)(89)(90)(91) and possibly even astrocytes (92).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia engage in constructive pruning to maintain synaptic and functional specialization during critical developmental phases and in neurogenesis (Matcovitch-Natan et al, 2016;Schafer and Stevens, 2015). In contrast, toxic pruning by microglia results from excessive immune activation and aggressive neural signaling (eg, during prenatal infections and severe stress) and appears to move the trajectory toward synaptic destruction or aberrant synaptic construction (Brites and Fernandes, 2015).…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 99%
“…Microglia once activated are critically involved in neuronal events at various stages in development and adulthood, including synaptic remodeling to improve neuronal network signaling (Schafer and Stevens, 2015). An increasing body of evidence suggests a link between microglia and the microbiota-gut-brain axis which has implications for many stress-related and neurodegenerative disorders There is a close link between HPA axis activation and the regulation of the peripheral and central immune responses, leading to monocyte priming and trafficking, subsequent alterations in microglia phenotype and, ultimately resulting in neuroinflammation.…”
Section: Microbiota As a Regulator Of Neuroimmune Functionmentioning
confidence: 99%